Functioning of a family with a child suffering from cystic fibrosis and short bowel syndrome - case study - Świerczyńska, Justyna; Mazur, Agnieszka; Chojnowska-Ćwiąkała, Izabela; Podosek, Agnieszka (Current Problems of Psychiatry, 2018)
This article presents the problem of the functioning of a family with a child suffering from two painful, chronic and incurable diseases - cystic fibrosis and short bowel syndrome. Its aim is to learn about the impact of these diseases on the occurrence and course of mental disorders in a child and on the functioning of the whole family in which such a child is brought up. Like any long-term illness of a child, it has influenced changes in the functioning of the family system. The parents’ functioning and the flexibility of the family system conditioned the acceptance of the diagnosis and determined further participation of the family in the treatment process. This article also discusses the risk of unfavorable attitudes of parents towards the child's illnesses, which may contribute to the development of mental disorders in the child patient, as well as in his/her parents or siblings. In the process of treatment and rehabilitation, the necessity for cooperation of medical staff, the patient and his/her parents has been emphasised.